Cross-Methodological Approach to Realization of Marketing Analytical Function - A. L. Beloborodova; N. V. Kalenskaya (Вестник Российского экономического университета имени Г. В. Плеханова)
The article explains the necessity to use cross-methodological approach to realization of marketing analytical function that combines methodology of classical marketing research and DataScience methodology. The explanation is based on results of literature analysis, which studies trends of DataDriven marketing development and DataScience; HeadHunter research dealing with assessing the compliance of the competence profile of specialist in the field of analytical marketing with demands of labour market and on results of the authors’ research in the present sphere. Comparative appraisal of efficiency of using classical methods of marketing research and DataScience methodology was conducted at enterprises; benefits and drawbacks of each of them were identified; similar and distinguishing stages of these approaches were found and efficiency of their integration was proved. Progress of Russian companies in realization of marketing analytical function by using DataDriven culture was estimated. Two principle reasons hindering the process of marketing based on data introduction to Russian organizations were named, i.e. non-compliance of competence profile of marketers-analysts//with market demands and uncoordinated investment in technologies aiming at DataDriven approach introduction into the company.